E-cigarette use and smoking reduction or cessation in the 2010/2011 TUS-CPS longitudinal cohort. (December 2016) - Shi, Yuyan; Pierce, John; White, Martha; Vijayaraghavan, Maya; Compton, Wilson; Conway, Kevin; Hartman, Anne; Messer, Karen
Abstract Background Electronic cigarettes (e-cigarettes) are heavily marketed and widely perceived as helpful for quitting or reducing smoking intensity. We test whether ever-use of e-cigarettes among early adopters was associated with: 1) increased cigarette smoking cessation; and 2) reduced cigarette consumption. Methods A representative cohort of U.S. smokers (N = 2454) from the 2010 Tobacco Use Supplement to the Current Population Survey (TUS-CPS) was re-interviewed 1 year later. Outcomes were smoking cessation for 30+ days and change in cigarette consumption at follow-up. E-cigarettes use was categorized as for cessation purposes or for another reason. Multivariate regression was used to adjust for demographics and baseline cigarette dependence level. Results In 2011, an estimated 12 % of adult U.S. smokers had ever used e-cigarettes, and 41 % of these reported use to help quit smoking. Smokers who had used e-cigarettes for cessation were less likely to be quit for 30+ days at follow-up, compared to never-users who tried to quit (11.1 % vs 21.6 %; ORadj = 0.44, 95 % CI = 0.2–0.8). Among heavier smokers at baseline (15+ cigarettes per day (CPD)), ever-use of e-cigarettes was not associated with change in smoking consumption. Lighter smokers (<15 CPD) who had ever used e-cigarettes for quitting had stable consumption, while increased consumption was observed among all other lighter smokers, although this difference was not statistically significant. Conclusions Among early adopters, ever-use of first generation e-cigarettes to aid quitting cigarette smoking was not associated with improved cessation or with reduced consumption, even among heavier smokers.